Retrospectives on factors influencing inclusive opportunities for college students with extensive support needs. Issue 12 (1st December 2016) - Orlando, Ann-Marie; Klinepeter, Elizabeth; Foster, Megan
ABSTRACT: Current U.S. legislation calls for students with disabilities to be involved and make progress in general education curriculum. Despite the legislation, students with extensive support needs continue to be segregated from their peers and post-school outcomes remain dismal for this population of students. The purpose of this retrospective study was to explore the perceptions of two students with extensive support needs and their caregivers regarding factors that contributed to their involvement and progress in the general education curriculum and eventual enrolment in four-year, post-secondary institutions in the United States. Findings related to the role of participants' perceptions of self, participants' engagement in advocacy roles and activities, and specific human and material supports that both facilitated and acted as barriers to education in the general curriculum emerged as recurrent themes. Limitations of the study and suggestions for future research and practice are presented.